Synthesis and evaluation of nitrochromene derivatives as potential antileishmanial therapeutics through biological and computational studies - Niloofar Javid; Ali Asadipour; Ehsan Salarkia; Mohammad Amin Langarizadeh; Fatemeh Sharifi; Mohammad Mahdavi; Bagher Amirheidari; Aida Iraji; Hojjat Rezaiezadeh; Gholamreza Hassanpour; Yaghoub Pourshojaei (Scientific Reports)
Abstract Leishmaniasis is a parasitic disease caused by protozoan organisms belonging to the Leishmania genus, affecting many individuals worldwide, with the burden surpassing one million cases. This disease leads to considerable morbidity and mortality, predominantly within tropical and subtropical regions. The current therapeutic options for leishmaniasis are far from ideal, as they fail to achieve a level of efficacy that can be deemed universally effective. The primary drawbacks of existing treatments include severe side effects, substantial toxicity, high financial costs, extended treatment regimens, and the discomfort associated with injectable forms of administration. Additionally, the growing issue of drug resistance presents a formidable challenge, further complicating disease management and control efforts. In light of these limitations, developing new therapeutic agents that can effectively disrupt the parasite’s life cycle at multiple stages is of paramount importance. This study endeavors to address this critical need by focusing on the design and synthesis of a series of novel compounds. Fifteen derivatives incorporating the nitrochromene pharmacophore were meticulously synthesized using the Henry reaction. After synthesizing these derivatives, a comprehensive evaluation of their biological activity against L. tropica was undertaken. This assessment employed both in vitro techniques to directly observe the compounds’ effects on the parasite and in silico methods, specifically molecular docking studies, to predict and analyze the interaction between the synthesized compounds and various target proteins of the parasite. The dual approach of combining experimental and computational methods aims to provide a robust understanding of the compounds’ mechanisms of action and their potential as effective anti-leishmanial agents. This integrative strategy not only enhances the reliability of the findings but also offers valuable insights that could guide future drug development efforts in combating leishmaniasis.